دور منظمة شنغهاي للتعاون في إنهاء حالة الأحادية القطبية وموقفها من الأزمة السّورية - محمود, يوسف عبد العزيز; شريقي, طرفة; زيتي, اياد بدر (Latakia University Journal - Economic and Legal Sciences Series, 2015)
تعتبر منظمة شنغهاي للتعاون من المنظمات الإقليمية الحديثة نسبياً حيث أعلن عن قيامها رسمياً في عام 2001، وتضم في صفوفها كل من (الصين، روسيا، وكازاخستان، أوزباكستان، طاجيكستان وقيرغيزستان) بصفة أعضاء دائمين، لقد حققت منظمة شنغهاي للتعاون مكانة دولية كبيرة جداً خلال السنوات الماضية، من حيث إمكانيات الدول التي تضمها من النواحي الاقتصادية والسياسية والعسكرية، وفي ظل الأزمة التي تعاني منها سورية والضغوط والعقوبات الخارجية، والإستراتيجية الجديدة التي اتخذتها الحكومة السورية والتي تقضي بالتوجه شرقاً، تشكل منظمة شنغهاي للتعاون مجالاً دولياً واسعاً أمام سورية للتخلص من الضغوط والعقوبات الغربية، وسيلقي هذا البحث الضوء على منظمة شنغهاي للتعاون، وموقفها من الأزمة السورية الراهنة وأبعاد مواقف دولها خاصة الصين وروسيا. The Shanghai Cooperation Organization (SCO) is considered relatively a modern regional organization which was announced officially in 2001; it included all of China, Russia, Kazakhstan, Uzbekistan, Tajikistan and Kyrgyzstan (as permanent members, the (SCO) occupied a very important position in the world several years ago, via the capacities of its countries in economic, political and military forces. In the light of the current crisis afflicting Syria and the pressures and foreign sanctions upon it, in addition to the new strategy adopted by the Syrian government, which stipulates "going east", the Shanghai Cooperation Organization shaped broad international scope for Syria to get rid of the pressure and Western sanctions. This research will try to shed light on the (SCO) and its attitude toward Syrian crisis and the implications of the stands of some countries, especially China and Russia.